Analisis Kelayakan Pengembangan Usaha Pasta Kangen Jupiter dan Mogot Jakarta Barat dengan Menggunakan Metode Capital Budgeting Tahun 2019-2023 - Ni Puthu Eka Wardani Haliasih; Pambuko Naryoto (Reviu Akuntansi, Manajemen, dan Bisnis, 2021)
Purpose: This study aimed to determine the feasibility of establishing the Pasta Kangen Jupiter dan Mogot Jakarta Barat in West Jakarta. Research methodology: The assessment is reviewed with Capital Budgeting in Optimistic, Moderate, and Pessimistic versions. Several methods include Payback Period, Net Present Value, Profitability Index, Average Rate of Return, Internal Rate of Return, dan Discounted Payback Period. Results: Based on the results of calculations using the Optimistic and Moderate Version of Capital Budgeting method, Pasta Kangen Jupiter Daan Mogot Jakarta Barat business in West Jakarta is feasible to run, while the Pessimistic Version is not feasible to run.